A DESCRIPTIVE STUDY ON OESOPHAGEAL CANCER IN HOSPITAL UNIVERSITI SAINS MALAYSIA - Siti Azrin Ab Hamid; Wan Nor Asyikeen Wan Adnan; Norsa’adah Bachok; Suhaili Mohd Sidek (Asian Journal of Medicine & Health Sciences, 2020)
Background: Oesophageal cancer is one of the cancer-related deaths in Malaysia. To date, neither the incidence nor the prevalence of oesophageal cancer has been documented especially in Kelantan, Malaysia. Objective: This study aimed to determine the basic features of oesophageal cancer patients registered in Hospital Universiti Sains Malaysia (USM). Methodology: A retrospective cohort study was carried out where the records of 55 oesophageal cancer patients registered in Hospital USM were retrospectively reviewed. The oesophageal cancer patients aged above 18 years old were included in the study whereas the patients with an incomplete medical record were excluded. Descriptive analysis was used. Results: The mean age (standard deviation) of oesophageal cancer patients was 63.5 (12.3) years. Thirty five of oesophageal cancer patients were males (63.6%) while other 20 patients were females (36.4%). Out of 55 patients, 45 of them were above 60 years of age (81.8%). Smoking was found in 42 oesophageal cancer patients (76.4%). Dysphagia was the main presenting symptom in all patients. Adenocarcinoma was the commonest histology type among oesophageal cancer patients (52.8%). Conclusion: Oesophageal cancer developed more in older and male patients. Most patients presented with common symptom of dysphagia and adenocarcinoma type of cancer.